2014
DOI: 10.1093/humrep/deu040
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of three sperm DNA damage assays and sperm nuclear protein content in couples undergoing assisted reproduction treatment

Abstract: N/A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
1
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 92 publications
4
83
1
7
Order By: Relevance
“…However, studies examining the effect of high SDF on assisted conception fertilization, embryo development, pregnancy, miscarriage, and birth outcomes report conflicting results; some studies report a correlation between SDF and outcomes for both in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) cycles (Collins et al, 2008;Robinson et al, 2012), others that IVF but not ICSI outcomes are influenced (Bungum et al, 2007;Zini, 2011;Osman et al, 2015), and others have found no clear association with either assisted fertilization method (Esbert et al, 2011;Ni et al, 2014). These inconsistencies may in part be attributed to study design and the use of different assays, with a recent study reporting that Comet and TUNEL assays were more predictive of clinical outcomes than SCSA (Simon et al, 2014). The use of flow cytometry in SCSA makes standardization difficult because of a degree of user-dependent skill and data interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies examining the effect of high SDF on assisted conception fertilization, embryo development, pregnancy, miscarriage, and birth outcomes report conflicting results; some studies report a correlation between SDF and outcomes for both in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) cycles (Collins et al, 2008;Robinson et al, 2012), others that IVF but not ICSI outcomes are influenced (Bungum et al, 2007;Zini, 2011;Osman et al, 2015), and others have found no clear association with either assisted fertilization method (Esbert et al, 2011;Ni et al, 2014). These inconsistencies may in part be attributed to study design and the use of different assays, with a recent study reporting that Comet and TUNEL assays were more predictive of clinical outcomes than SCSA (Simon et al, 2014). The use of flow cytometry in SCSA makes standardization difficult because of a degree of user-dependent skill and data interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…Another reason for reduced expression of PLCζ could be related to oxidative stress. DNA and RNA are common targets of reactive oxygen species [37] which might have a critical effect on embryo quality and pregnancy rates in IVF/ICSI treatments [38][39][40] and increased upon heat stress or in varicocele condition [30,41].…”
Section: Discussionmentioning
confidence: 99%
“…Появились публикации о том, что высокий уровень повреждения ДНК связан с нарушением дробления эмбриона, высокой частотой спонтанных абортов и по-вторными потерями беременности после ВРТ [39][40][41][42].…”
Section: Objective Study Of the Correlation Between Abnormal Chromatunclassified
“…В последнее десятилетие опубликованы многочи-сленные исследования, авторы которых пытаются уста-новить корреляцию между фрагментацией ДНК и ста-тусом хроматина [30,[42][43][44][45][46].…”
Section: Objective Study Of the Correlation Between Abnormal Chromatunclassified
See 1 more Smart Citation